2019
DOI: 10.1016/j.ipej.2019.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Markers of ventricular repolarization as an additional non-invasive electrocardiography parameters for predicting ventricular tachycardia/fibrillation in patients with Brugada Syndrome – A systematic review and meta-analysis

Abstract: BackgroundControversies surrounded the management of asymptomatic Brugada syndrome. Prognostication using electrophysiology study (EPS) is disputable. Non-invasive parameters may be a valuable additional tool for risk stratification. We aim to evaluate the use markers of ventricular repolarization including Tpeak-to-Tend (TpTe), Tpe Dispersion, TpTe/QT ratio, and QTc interval as additional non-invasive electrocardiography parameters for predicting ventricular tachycardia/fibrillation in patients with Brugada s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This would suggest altered repolarization playing an important role in mediating ventricular arrhythmogenesis in this subgroup (31)(32)(33)(34). It is hypothesised that QTc prolongation reflects the increased dispersion in transmural ventricular repolarization, thus increase the risk of VT/VF (35)(36)(37)(38)(39)(40)(41)(42). Moreover, we found that paediatric/young patients had a higher QRS axis, in keeping with previous demonstrations of right axis deviation in younger patients but this variable was not a predictor of arrhythmic events.…”
Section: Brugada Syndrome In the Youngsupporting
confidence: 88%
“…This would suggest altered repolarization playing an important role in mediating ventricular arrhythmogenesis in this subgroup (31)(32)(33)(34). It is hypothesised that QTc prolongation reflects the increased dispersion in transmural ventricular repolarization, thus increase the risk of VT/VF (35)(36)(37)(38)(39)(40)(41)(42). Moreover, we found that paediatric/young patients had a higher QRS axis, in keeping with previous demonstrations of right axis deviation in younger patients but this variable was not a predictor of arrhythmic events.…”
Section: Brugada Syndrome In the Youngsupporting
confidence: 88%
“…Importantly, Tp-e was found to be the most promising ECG marker together with QTc interval in predicting malignant arrhythmias among BS patients. However, there is a need to assess the cut-off for the Tp-e value, which significantly increases the risk of life-threatening arrhythmias [ 117 ]. Interestingly, when the BS typical ECG pattern was observed in precordial leads V1–V3, it was simultaneously revealed that the Tp-e interval in V1 lead was significantly higher among patients with malignant arrhythmias.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, we do not recommend the routine use of indices of ventricular repolarization for COVID-19 patients who are not otherwise at risk of QT prolongation. This recommendation was not solely based on the current findings, as there are significant methodological concerns about the usefulness of these parameters for predicting ventricular arrhythmias 26 .…”
Section: Discussionmentioning
confidence: 97%